The Effect Of Contextual Teaching and Learning Model Using Cycle Cardboard Media on Natural Science Learning Outcome - Ongke Ageng Pamorti (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of the Contextual Teaching and Learning modelusing Cycle Cardboard media on natural science learning outcomes of four grade studentsof Kembaran Candimulyo Primary School Magelang. This type Pre Experimental researchwith One Group Pretest Posttest model. The method of data collection is done usinglearning outcomes pretest and posttest tests in the form of multiple choice questions. Thesampling technique used total sampling (exhautive sampling). Data was collected throughpretest-posttest and than analyzed using Paired Sample in the SPSS 25.00 program forwindows.The results showed that the Contextual Teaching and Learning model usingCycle Cardboard media had effect on student natural science learning outcomes. This isevidenced from the result of the analysis of the Paired Sample in the experimental classwith a probability value of sig (2-tailed) 0,001 (0,001<0,05). Based on the result of theanalysis and discussion, there is a difference in the average score pretst and posttest,namely the result pretest 66,8 and posttest 78,15, both of which have a difference of 11,35.The result of study concluded that the use of the Contextual Teaching and Learning modelusing Cycle Cardboard media had effect on student natural science learning outcomes.